Once upon a time, there was a fabulous funambulist…: what children learn about the “high-level” vocabulary they encounter while listening to stories - Houston-Price, Carmel; Howe, Jodie A.; Lintern, Natalie J. (Frontiers in Psychology, 2014)
Previous research has shown that listening to stories supports vocabulary growth in preschool and school-aged children and that lexical entries for even very difficult or rare words can be established if these are defined when they are first introduced. However, little is known about the nature of the lexical representations children form for the words they encounter while listening to stories, or whether these are sufficiently robust to support the child’s own use of such ‘high-level’ vocabulary. This study explored these questions by administering multiple assessments of children’s knowledge about a set of newly-acquired vocabulary. Four- and 6-year-old children were introduced to nine difficult new words (including nouns, verbs and adjectives) through three exposures to a story read by their class teacher. The story included a definition of each new word at its first encounter. Learning of the target vocabulary was assessed by means of two tests of semantic understanding – a forced choice picture-selection task and a definition production task – and a grammaticality judgment task, which asked children to choose between a syntactically-appropriate and syntactically-inappropriate usage of the word. Children in both age groups selected the correct pictorial representation and provided an appropriate definition for the target words in all three word classes significantly more often than they did for a matched set of non-exposed control words. However, only the older group was able to identify the syntactically-appropriate sentence frames in the grammaticality judgment task. Further analyses elucidate some of the components of the lexical representations children lay down when they hear difficult new vocabulary in stories and how different tests of word knowledge might overlap in their assessment of these components.